Assessment of bone health in pre-dialysis CKD patients based on TBS reference range for the Chinese population - Wu, Biao; Wu, Huanhua; Wang, Zheng; Tan, Zhiqiang; Guo, Bin; Shang, Jingjie; Cheng, Yong; Zeng, Chunyuan; Jiang, Yuanfang; Cai, Qijun; Gong, Jian; Xu, Hao (Frontiers in Medicine, 2025)
BackgroundPre-dialysis chronic kidney disease (CKD) Patients show a markedly elevated risk of fractures, and BMD assessments offer only limited insights into their bone health. The trabecular bone score (TBS), a newly introduced parameter for evaluating bone microarchitecture, is recommended for studying bone health under this context.MethodsA total of 46 subjects were included in the control group, and 136 patients were included in the CKD group. All participants underwent laboratory examinations, Dual energy X-ray absorptiometry (DXA) scans, and medical history reviews. The relationships between TBS and demographic characteristics, history of fractures, LS-BMD, FN-BMD, and laboratory parameters were analyzed.ResultsAge, gender, and BMI were matched between the control and CKD groups (P > 0.05). The control group had an average age of 64.96 ± 7.76 years with 27 females (58.70%), while the CKD group had an average age of 64.42 ± 10.90 years with 66 females (48.53%). Among the CKD group, 43 patients had fractures. In both control and CKD participants, when BMD was normal or osteopenia, TBS frequently indicated partially reduced bone microarchitecture or reduced bone microarchitecture, a statistically significant finding (P < 0.05). In CKD fracture patients with normal or osteopenic BMD, several patients had TBS classified as degraded or degraded trabecular bone, and among this population, the number of individuals classified as having partially reduced bone microarchitecture or reduced bone microarchitecture based on the TBS (China reference range) is higher than the number classified under the TBS (META reference range). Furthermore, except for the FN-BMD (Osteoporosis) group, TBS-incorporated models significantly improved fracture discrimination across other groups (P < 0.05).ConclusionIn pre-dialysis CKD patients with normal or reduced BMD, TBS is significantly associated with fracture risk. Additional evaluation of bone microstructure using TBS enhances fracture risk identification, particularly in patients with relatively high BMD.